A Moving Theory: Remembering the Office of Scholar - Olivia Barr (Law Text Culture, 2010)
‘May it please the Court, I appear for the State.’ As a legal practitioner and government solicitor, this phrase was part of my former everyday. Known as making an appearance, this formal phrase communicates the action of presenting oneself in court. To appear, it must be remembered, is an action of coming forward into view: an act of becoming visible. This is a movement into visibility. In this formal appearance, the movement into visibility is a movement mediated by office. For it was through the office of government solicitor that I spoke for and performed for the state. More than just performance, however, the duties and responsibilities of office constructed an environment where I could not speak of law in ways I wanted to. For me, this meant I was limited in my ability to speak of Aboriginal sovereignty, which was consistently framed as a challenge to the authority of the state. The role required by this particular office seemingly meant that this was an inappropriate issue. In effect, my speech was restricted. It was as if my performance for the state, through the office of government solicitor, had somehow rendered me inarticulate.